Synthesis, characterization and biological evaluation of novel benzimidazole derivatives. Issue 6 (12th April 2020) - Mahmood, Khalid; Akhter, Zareen; Asghar, Muhammad Adeel; Mirza, Bushra; Ismail, Hammad; Liaqat, Faroha; Kalsoom, Saima; Ashraf, Ahmad Raza; Shabbir, Muhammad; Qayyum, Muhammad Abdul; McKee, Vickie
Abstract: In search of achieving less toxic and more potent chemotherapeutics, three novel heterocyclic benzimidazole derivatives: 2-(1H-benzo[d]imidazol-2-yl)-4-chlorophenol (BM1), 4-chloro-2-(6-methyl-1H-benzo[d]imidazol-2-yl)phenol (BM2) and 4-chloro-2-(6-nitro-1H-benzo[d]imidazol-2-yl)phenol (BM3) with DNA-targeting properties, were synthesized and fully characterized by important physicochemical techniques. The DNA binding properties of the compounds were investigated by UV–Visible absorption titrations and thermal denaturation experiments. These molecules exhibited a good binding propensity to fish sperm DNA (FS-DNA), as evident from the high binding constants ( K b ) values: 1.9 × 10 5, 1.39 × 10 5 and 1.8 × 10 4 M ‒1 for BM1, BM2 and BM3, respectively. Thermal melting studies of DNA further validated the absorption titration results and best interaction was manifested by BM1 with Δ T m = 4.96 °C. The experimental DNA binding results were further validated theoretically by molecular docking study. It was confirmed that the molecules (BM1–BM3) bind to DNA via an intercalative and groove binding mode. The investigations showed a correlation between binding constants and energies obtained experimentally and through molecular docking, indicating a binding preference of benzimidazole derivatives with the minor groove of DNA. BM1 was the preferential candidate for DNA binding because of its flat structure, π–π interactions and less steric hindrance. To complement the DNA interaction, antimicrobial assays (antibacterial & antifungal) were performed. It was observed that compound BM2 showed promising activity against all bacterial strains ( Micrococcus luteus, Staphylococcus aureus, Enterobacter aerogenes and Escherichia coli ) and fungi ( Aspergillus flavus, Aspergillus fumigatus and Fusarium solani ), while rest of the compounds were active against selective strains. The MIC values of BM2 were found to be in the range of 12.5 ± 2.2–25 ± 1.5 µg/mL. Thus, the compound BM2 was found to be the effective DNA binding antimicrobial agent. Furthermore, the preliminary cytotoxic properties of synthesized compounds were evaluated by brine shrimps lethality assay to check their nontoxic nature towards healthy normal cells. Communicated by Ramaswamy H. Sarma Abstract : Highlights: New heterocyclic benzimidazole molecules were synthesized and characterized. FT–IR, 1 H and 13 C NMR, GC–MS, TOF–MS and single crystal X-ray diffraction and elemental analysis were used for structure elucidation. DNA binding propensity was assessed by spectroscopic and computational methods. Antibacterial and cytotoxic activities were also investigated.